Colour As Branding And Value Creation On The Small Medium Enterprise (Sme) Food Souvenir Packaging In Bandung, Indonesia - Swasty, Wirania (2023)
The food packaging design has improved significantly, allowing for more diverse colours. However, most Small Medium Enterprises (SMEs) in Bandung still lack inadequate and unattractive packaging designs. The first problem identified are the use of colours in product packaging helps with brand identification but fails to provide functional value when driven by emotional value. Secondly, using uncommon colours for brand visibility but resulting a negative impact for the brand. Thus, this study aims to examine the role of colours within branding and value creation in SME food packaging in Bandung; to discover the extent to which the perception of (un)common colours in packaging vary across local and international tourists; to evaluate consumer perception and attitudes toward the usage of the uncommon colour palette on SME food product packaging. This study used a qualitative approach. For data collecting, a comparison of multiple case studies, indepth interviews, and card sorting were conducted. Data analysis approach was inductive with thematic analysis. This study also suggests the application of palettes in food packaging and provides colour palette guidelines for SMEs' food packaging in Bandung. This study makes contributions to design literature by creating and communicating values to consumers by utilising colour on Packaging.